Clinical and epidemiological survey of tungiasis in Madagascar. Issue 50 (November 2022) - Rasoamialy-Soa Razanakolona, Lala; Raharisoa, Annie; Soankasina, Abel Hermann; De La Croix Jaonasoa, Jean; Nicolas, Patrick; Antilahy, Jimmy Anders; Chebbah, Dahlia; Akhoundi, Mohammad; Izri, Arezki
Abstract: Background: Tungiasis is a dermal parasitic infection, classified as a neglected tropical disease. Madagascar is one of endemic countries which have been committed for decades to control the tungiasis as a public health issue. Despite this medical importance, little is known about the prevalence and epidemiology of the disease in this country. Methods: A descriptive cross-sectional survey was performed in two endemic foci of Antananarivo and Toamasina. Results: In total, 2971 suspected individuals were surveyed. Of them, 643 individuals were excluded due to absence or refusing clinical examinations. Therefore, 2328 individuals with aforementioned criteria were clinically examined, 320 cases (13.7%) were found infected by Tunga penetrans . Of these 320 infected cases, 241 individuals came from rural regions against 79 from urban areas. The sex ratio of infected cases was 1.15 with an age average of 34.7 years old. Most of them were illiterate (185/320, 57.8%) with no habit of feet washing (210/320, 65.6%). The majority (198/320, 61.9%) inhabited in the houses constructed by falafa providing a suitable breeding location for Tunga ectoparasites. Based on clinical examination, most of the patients (298/320, 93.1%) had the lesions on their toes followed by those possessed the lesions on the plantar (140/320, 43.7%). The lesion stages of IV and V were observed in 49.1% (157/320) of visited patients which were more common in rural regions (86%) than in urban areas (14%). For treatment, removing the fleas using needle (122/320, 38.1%), followed by the application of petroleum (100/320, 31.2%) were among the most traditional remedies used by our patients. Conclusion: This investigation highlights a high burden of tungiasis in studied endemic foci in particular in rural regions. These results can be helpful in control management strategies against this parasitosis in Madagascar.